Investigation of the Oxidative Stress, the Altered Function of Platelets and Neutrophils, in thePatients with Peripheral Arterial Disease - Kurthy, Maria; Jancso, Gabor; Arato, Endre; Sinay, Laszlo; Lantos, Janos; Miklos, Zsanett; Balatonyi, Borbala; Javor, Szaniszlo; Ferencz, Sandor; Rantzinger, Eszter; Kovacs, Dora; Kovacs, Viktoria; et al. (IntechOpen, 2012)
None